การเรียนรู้ที่ส่งผลต่อประสิทธิภาพในการปฏิบัติงานของเจ้าหน้าที่พัสดุ มหาวิทยาลัยสงขลานครินทร์ - วันชัย ไชยทองคำ (มหาวิทยาสงขลานครินทร์, 2022)
Research on Learning Affecting Effective Employee Performance among Supplies Officers in Prince of Songkla University. This research objective were to study the learning level, the level of efficiency in the performance, compare the operational efficiency classified by personal factors and learning that affected the efficiency of the operations of supplies officers in Prince of Songkla University. This research was quantitative research by using the survey research with the sample group of supplies officers in Faculty of Medical Sciences at Prince of Songkla University, collected 176 samples and used stratified sampling by using questionnaires as a method. The statistics used in the data analysis in this research were frequency distribution, percentage, mean, standard deviation, Pearson's correlation and multiple linear regression. Results showed an overview of the learning level of supplies officers in Prince of Songkla University is at the high level, in terms of the specific learning was the highest level. An overview of the level of efficiency in the performance of supplies officers in Prince of Songkla University was also at the high level, in terms of the amount of work performance by the personnel was the highest level. The comparative analysis of the difference in opinions of supplies officers in Prince of Songkla University classified by personal factors showed that age, monthly income, work experience, educational, position and affiliated organization, significantly different at the 0.01 level and the marital status, significantly different at the 0.05 level, gender did not different. And the analysis of learning affecting the efficiency of supplies officers in Prince of Songkla University found that specific learning factors affect the efficiency of work, significant at the 0.01 level with a relatively high correlation.